RELATIONSHIP BETWEEN PHYSICAL WORKLOAD, SLEEP QUALITY, WORK CLIMATE, AND NOISE LEVEL WITH WORK FATIGUE IN ROLLING MILL WORKERS IN SIDOARJO STEEL INDUSTRY - Muhammad Faris Rasyid (The Indonesian Journal of Public Health, 2022)
Introduction: Every year 250 million work accidents occur and more than 160 million experience occupational diseases (ILO, 2013). One factor that causes work accidents is unsafe behavior caused by work fatigue. The purpose of the study was to analyze the relationship between physical workload, sleep quality, work climate, and noise with work fatigue in Rolling Mill Steel Industry section workers Sidoarjo. Methods: This study is an observational and analytical study with a cross-sectional design. The study population was 34 workers and a sample of 31 respondents were workers in the Rolling Mill section. The sampling technique used simple random sampling. Independent variables were physical workload, sleep quality, work climate, and noise. The dependent variable was fatigue. Spearman correlation test was used to determine the relationship between physical workload and work fatigue. A Chi-square test was used to determine the relationship between sleep quality, work climate, and noise with work fatigue. Result: The result showed (61,3%) workers experienced moderate physical workload, (61,3%) workers had good sleep quality, (64,5%) workers worked above work climate threshold limit value, (77,4%) workers worked above noise threshold limit value, and (48,5%) workers had normal fatigue. Statistical analysis shows physical workload (p = 0.031), sleep quality (continuity correction = 0.047), work climate (fisher exact = 0.002), and noise (fisher exact = 0.009) have a relationship with work fatigue. Conclusion: This study concludes that physical workload, sleep quality, work climate, and noise have a relationship with work fatigue.